2007
DOI: 10.1080/13880200701214847
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, Antifungal, and Cytotoxic Activities ofDistictis buccinatoria.

Abstract: The current study was undertaken to evaluate the in vitro antimicrobial and cytotoxic activity of six crude extracts obtained from the leaves and flowers of Distictis buccinatoria (DC.) A.H. Gentry (Bignoniaceae). Antimicrobial activity was tested against the Gram-positive bacteria Staphylococcus aureus, Streptococcus pyogenes, and Streptococcus faecalis; the Gram-negative bacteria Escherichia coli, Klebsiella pneumoniae, and Salmonella typhi; and the fungi Candida albicans, Trichophyton mentagrophytes, Tricho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Although, D. buccinatoria is used in traditional medicine for the treatment of inflammation related diseases, only cytotoxic, antimicrobial and antifungal activities had been described for integrate extracts from this plant (Rojas et al, 2007). This is the first report that confirms the traditional use of "Tonacaxochilt" as anti-inflammatory treatment.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although, D. buccinatoria is used in traditional medicine for the treatment of inflammation related diseases, only cytotoxic, antimicrobial and antifungal activities had been described for integrate extracts from this plant (Rojas et al, 2007). This is the first report that confirms the traditional use of "Tonacaxochilt" as anti-inflammatory treatment.…”
Section: Discussionmentioning
confidence: 77%
“…Distictis buccinatoria has been used, since, pre-Hispanic times for medical purposes (De la Cruz, 1964;Moreno, 1971). Now a days, empirical midwives and herbalists in the state of Morelos use the decoction of its leaves and flowers to treat cough, angina, inflammation, pharyngitis and coughs with blood (Rojas et al, 2007). Previous studies demonstrated that this plant shows anti-microbial activity against Staphylococcus aureus, Streptococcus pyogenes, Streptococcus faecalis, bacteria and Trichophyton mentagrophytes, Trichophyton rubrum dermatophytes, as well as cytotoxicity against cancerous line cell KB (Rojas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The multi-well plates were incubated for 72 h under the same conditions, after which, the cell concentration for each treatment was determined by quantifying the protein with the Lowry method. The results are expressed as the extract concentration that inhibited growth by 50%, i.e., the median inhibitory concentration (IC 50 ) relative to the negative control [34]. Values were estimated from the treatment semi-log concentrations versus the percentage of viable cells.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…A.H. Gentry (Bignoniaceae), is a native Mexican plant which has been used by empirical midwives and herbalists in the state of Morelos in Mexico to treat cough, angina, inflammation, pharyngitis, and coughs [5]. A.H. Gentry (Bignoniaceae), is a native Mexican plant which has been used by empirical midwives and herbalists in the state of Morelos in Mexico to treat cough, angina, inflammation, pharyngitis, and coughs [5].…”
Section: Distictis Buccinatoria Plantmentioning
confidence: 99%